Pulse crops as effective living mulches: An eco-conscious weed management approach - Rajakumar, D; Sabarinathan, KG; Gomathy, M; Ejilane, J; Ananthi, K; Vasantharaj, P (Plant Science Today, 2025)
The evolution of weed management strategies from basic cultural techniques to novel, integrated approaches reflects technological advancements that promise further improvements in weed management strategies, fostering more efficient and eco-friendly farming practices. Using legume crops as living mulches for weed suppression has gained considerable attention in agricultural systems. This method involves strategically planting leguminous cover crops as intercrops to inhibit weed growth and improve soil health, potentially boosting crop yields through reduced weed pressure and enhanced nutrient availability. The successful implementation of living mulches requires careful selection of crop species, optimal planting density, and appropriate management practices. Choosing compatible legumes, optimizing planting geometry and employing suitable termination methods are essential for maximizing the weed-suppressing and soil-enhancing benefits of living mulches. The efficacy of intercropping systems in controlling weeds largely depends on intercrop components' growth rate and duration. Weed management strategies rely on understanding plant interactions, including the competitive ability of main crops at various growth stages to inhibit weed expansion. While intercropping shows promise for enhancing crop dominance over weeds, weed control efficiency varies among different intercrops due to factors affecting the intercrop-weed relationship. Smallholder farmers find this practice appealing for improving labour productivity and land use through intensification and resource utilization for maximum yield. Research on developing genotypes suitable for weed suppression and studies on combined herbicide applications and optimal dosage determination for effective control of mixed weed flora is necessary. The shift towards integrating pulse crops as a cornerstone in weed management strategies presents a promising avenue for research and application. The comparative analysis underscored in this review showcases the capacity of legumes to offer a viable alternative to synthetic herbicides and mechanical controls, paving the way for their increased adoption in diverse farming systems.